Identification and characterization of the primary infectious agents associated with ovine ulcerative balanoposthitis and vulvovaginitis in South Africa - Van Vuuren, Moritz (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2003.